2022
DOI: 10.1590/1413-81232022279.17542021en
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of primary health care for patients with diabetes based on the PMAQ-AB

Abstract: This article aims to present a proposal for making the instruments used in the three cycles of the PMAQ-AB compatible and to analyze the information on access, coverage, structure, organization and provision of services in PHC related to care for DM in Brazil, according to regions, from the perspective of family health professionals and users. We performed an analysis of the degree of compatibility of the PMAQ-AB questions (2012, 2014 and 2017). To analyze the temporal evolution of the components, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Os resultados dos indicadores da ação estratégica de Quanto ao acompanhamento e à relevância da solicitação de exames de HbA1c para pessoas com diabetes, evidenciou-se nos estudos que a solicitação foi considerada adequada, no entanto 30% dos usuários não receberam a solicitação do exame (23) e, em outro estudo, 30% relataram que não fizeram o exame (24) . Ainda nesse sentido, observaram-se alterações em mais da metade dos exames de usuários com diabetes, indicando a falta de controle da patologia de maneira adequada.…”
Section: Resultsunclassified
“…Os resultados dos indicadores da ação estratégica de Quanto ao acompanhamento e à relevância da solicitação de exames de HbA1c para pessoas com diabetes, evidenciou-se nos estudos que a solicitação foi considerada adequada, no entanto 30% dos usuários não receberam a solicitação do exame (23) e, em outro estudo, 30% relataram que não fizeram o exame (24) . Ainda nesse sentido, observaram-se alterações em mais da metade dos exames de usuários com diabetes, indicando a falta de controle da patologia de maneira adequada.…”
Section: Resultsunclassified
“…Regarding the follow-up and relevance of requesting HbA1c tests for people with diabetes, studies showed that the request was considered adequate, however, 30% of users did not receive the test request (23) and, in another study, 30% of users reported that they did not do the test (24) . Also in this sense, alterations were observed in more than half of the tests of users with diabetes, indicating the lack of adequate control of the pathology.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto al seguimiento y a la pertinencia de la solicitud de pruebas de HbA1c para personas con diabetes, los estudios demostraron que la solicitud fue considerada adecuada, sin embargo, el 30% de los usuarios no recibieron la solicitud de la prueba (23) y, en otro estudio, el 30% informaron que no se realizaron la prueba (24) .…”
Section: Frente a Ese Aumento Las Regiones Norte Y Centrounclassified